Interfaith Marriage in the Perspective of Islamic Jurisprudence and Compilation of Islamic Law - Saleh, Muhammad; Sufiati, Sufiati; Basri, St Risnawati; Satrianingsih, A.; Hamzah, Nur Asia (Journal of Family Law and Islamic Court, 2022)
Interfaith Marriage in the Perspective of Islamic Jurisprudence and Compilation of Islamic Law is the title of this study. This study examines the law of interfaith marriage through the lens of Islamic jurisprudence and the Compilation of Islamic Law. The library research method was used in this study, which involves reviewing and analyzing data obtained from literary sources such as books, papers, chapters, journals, and so on concerning the law of interfaith marriages in order to obtain accurate data. According to the findings of this study, the law on interfaith marriage is divided into several parts: a) the law on Muslim men marrying women who are experts in the book, which most scholars allow and some consider makruh. b) The Ulama agree that it is haram for a Muslim man to marry a polytheistic woman. c) The Law Concerning Muslim Women Who Marry Non-Muslim Men. Islamic jurists consider this marriage to be forbidden by Islam, regardless of whether the prospective husband is from the ahlul kitab (Jews and Christians) or a follower of other religions with holy books, such as Hinduism and Buddhism, or a believer in other religions' beliefs that do not have Scripture. Under any circumstances, Muslim women are not permitted to marry men who are not of their religion, whether they are of the book or not. The Compilation of Islamic Law forbids marriage between men and women who are not Muslims. Marriage is hampered by religious differences in the compilation of Islamic laws. Marriage, different religions, Islamic jurisprudence, a compilation of Islamic laws are all keywords.--Penelitian ini berjudul Perkawinan Beda Agama dalam Perspektif Fikih Islam dan Kompilasi Hukum Islam (KHI). Penelitian ini membahas tentang bagaimana hukum perkawinan beda agama dalam pandangan fikih Islam dan bagaimana hukum perkawinan beda agama dalam  perspektif Kompilasi Hukum Islam (KHI). Adapun metode yang digunakan dalam penelitian ini adalah metode penelitian pustaka yaitu penelitian dengan cara mengkaji dan menelaah data yang diperoleh dari sumber kepustakaan seperti buku-buku, makalah-makalah, artikel, jurnal dan lain sebagainya yang menyangkut tentang hukum perkawinan beda agama, sehingga akan mendapatkan data yang tepat. Hasil penelitian ini dapat disimpulkan bahwa Hukum perkawinan beda agama terbagi menjadi beberapa bagian, yaitu: a) Hukum laki-laki muslim menikah dengan perempuan ahli kitab yaitu kebanyakan ulama cenderung membolehkan perkawinan tersebut dan sebagian mereka menganggapnya makruh. b) Hukum perkawinan laki-laki muslim dengan perempuan musyrik yakni para Ulama sepakat bahwa seorang pria muslim diharamkan menikah dengan seorang wanita musyrikah. c) Hukum muslimah menikah dengan laki-laki non muslim, Para ahli hukum Islam menganggap perkawinan ini dilarang oleh Islam, baik itu calon suami dari ahli kitab (Yahudi dan Kristen) ataupun pemeluk agama lain yang mempunyai kitab suci seperti Hindu dan Budha ataupun pemeluk agama kepercayaan yang tidak memiliki Kitab suci. Perempuan muslimah tidak boleh menikah dengan laki-laki lain selain dari agamanya baik itu dari ahli kitab ataupun lainnya dengan situasi apapun. Adapun Kompilasi Hukum Islam (KHI) tidak membolehkan untuk menikah dengan laki-laki atau perempuan selain Islam. Perbedaan agama dalam kompilasi hukum islam menjadi penghalang untuk melangsungkan pernikahan.